AROMATERAPI GINGER OIL UNTUK MENURUNKAN DERAJAT MORNING SICKNESS PADA IBU HAMIL TRIMESTER I - Martina Ekacahyaningtyas; Dita Kuncoro Murti; Ari Febru Nurlaily (Universitas Kusuma Husada Surakarta, 2022)
Morning sickness or nausea and vomiting in the morning usually occurs in first trimester pregnant women at 6-12 weeks of gestation. Continuous morning sickness can have a negative impact on pregnant women, namely hyperemesis gravidarum. This has a bad impact on pregnant women. One of the treatments that can be done is through ginger oil aromatherapy which has a strong aromatic stimulus and can control nausea and vomiting by increasing intestinal peristalsis. This study aims to determine the effectiveness of the use of ginger oil aromatherapy against morning sickness in first trimester pregnant women. The research design used was a quasi-experimental approach with pre-test and post-test without control group design. Data analysis in this study used the Wilcoxon test. The results of this study indicate a p value of 0.000 (p value <0.05), which means that there is an effect of ginger oil aromatherapy on morning sickness in first trimester pregnant women. The conclusion of this study is ginger oil aromatherapy is effective in reducing the degree of morning sickness in first trimester pregnant women.